A comparative study between vapor phase polymerized PPy and PEDOT - Thermoplastic polyurethane composites for ammonia sensing. (5th March 2021) - Fernandez, Frances Danielle M.; Khadka, Roshan; Yim, Jin-Heong
Abstract: In this study, in situ vapor phase polymerization (VPP) of (1) 3, 4-ethylenedioxythiophene (EDOT) and (2) pyrrole (Py) on an oxidant-impregnated thermoplastic polyurethane (TPU) substrate was conducted to produce a (1) PEDOT-TPU hybrid film and (2) PPy-TPU hybrid film. Scanning electron microscopy, atomic force microscopy, and energy dispersive x-ray spectroscopy confirmed the formation of uniform, rough surfaces of PPy and PEDOT on the TPU matrix. Both PPy-TPU and PEDOT-TPU films showed excellent thermal stability across the temperature range of 300 °C–400 °C and enhanced mechanical properties, depicted by very high stress and strain values. The performance of these hybrid films to detect ammonia (NH3 ) gas was investigated and then optimized under the effects of varying temperature, ammonia concentration, and monomer type used. The PEDOT-TPU and PPy-TPU showed remarkable sensitivity to NH3 gas, with coefficients of variation of 0.9858 and 0.9653, respectively. Particularly, the PEDOT-TPU sensor showed higher responsiveness to NH3 at higher operating temperatures owing to its higher surface roughness and thermal stability. These flexible, stretchable, smart conducting polymer composite materials fabricated using VPP are therefore potential candidates for monitoring toxic and non-toxic gases. Graphical abstract: Image 1 Highlights: PEDOT-TPU and PPy-TPU based ammonia sensors were fabricated by in situ vapor phase polymerization. The sensors showed high sensitivity, electrical stability, good selectivity, and repeatable response towards NH3 . These smart conducting polymer composite materials are potential candidates for monitoring toxic and non-toxic gases.